DEVELOPMENT OF HETEROLOGOUS SKUALENA PRODUCTION FROM VIRGIBACILLUSSALARIUS 19.PP.SC1.6 BACTERIA IN ESCHERICHIA COLI BL21(DE3) - Indira Laily Nurdin, Irishtsany
Indonesia is a country with a diversity of microorganisms that have various potentials in the industrial sector. One example is the bacteria Virgibacillus salarius 19.PP.Sc1.6 found in the South Java Sea. This bacteria is known to have the sqs gene that can produce squalene, a molecule that is widely used in the cosmetics industry. The value of Indonesia's squalene imports which always increases every year indicates that the high demand for squalene cannot be met by domestic production, so alternative sources of squalene are needed that can be produced efficiently and sustainably. This study aims to develop heterologous squalene production in E. coli BL21(DE3) bacteria by isolating the sqs gene from V. salarius 19.PP.Sc1.6, constructing the sqs gene in an expression vector using variations in the ribosome binding site (RBS) sequence, and optimizing squalene production with variations in the concentration of isopropyl ?- d-1-thiogalactopyranoside (IPTG). The sqs gene from V. salarius 19.PP.Sc1.6 was successfully isolated with a nucleotide base length of 822 bp and had an identical sequence to the sqs gene from the whole genome sequencing results of V. salarius 19.PP.Sc1.6, showing no mutations. Furthermore, the construction of the BSqs expression vector was carried out by combining the sqs gene isolate and the B04-T7-AmpHigh plasmid backbone using the BASIC assembly method through the use of RBS linker and neutral linker. The BASIC assembly method allows the construction of plasmids in a modular manner using bioparts and DNA linkers that can be easily combined. In this study, the ability of 3 RBS with different sequences was tested which then produced 3 plasmid variations; BSqs1, BSqs2, and BSqs3. After being assembled and validated by PCR, the BSqs plasmid was transformed into E. coli BL21(DE3) bacteria that already contained the JBEI-3085 plasmid. The JBEI-3085 plasmid contains precursor genes in the squalene biosynthesis pathway, so its addition is expected to increase the number of precursor molecules to produce squalene. The recombinant E. coli BL21(DE3) was then used for heterologous squalene production, the levels of which were quantified using HPLC. The testing stage of the effect of RBS sequence variation showed that this treatment had a significant effect (p < 0,05) on squalene production. U3R3 produced 191,43 mg/L of squalene, about 12,5% more than U2R2 and 16,6% more than U1R1. Testing the effect of IPTG concentration variation was then carried out on cultures containing U3R3. Four variations of IPTG concentration, 0; 0,05; 0,1; and 0,2 mM, were used to find the best concentration to maximize squalene production. The addition of IPTG will regulate squalene production by inducing the expression of T7 RNA polymerase which is responsible for transcribing the sqs gene in the BSqs plasmid controlled by the T7 promoter. The highest squalene production was produced by the use of 0,05 mM IPTG (142,08 mg/L), but there was no significant difference in the results of squalene production at each IPTG concentration (p> 0,05). This study succeeded in developing heterologous squalene production in E. coli BL21(DE3) bacteria by utilizing the sqs gene from the Indonesian South Java Sea bacteria, V salarius 19.PP.Sc1.6. The use of U3R3 and IPTG of 0,05 mM was the best combination of treatments in producing squalene in this study.